Hubungan Pembelajaran Jarak Jauh dan Gangguan Somatoform dengan Tingkat Stres Mahasiswa UIN Syarif Hidayatullah Jakarta - Putri, Rizky Muharany; Oktaviani, Anissa Dwi; Utami, Adi Setya Frida; maturrohmah, Ni; Addiina, Halwa Ainaya; Nisa, Hoirun (UI Scholars Hub, 2020)
Background. Physical distancing to prevent transmission of COVID-19 at the beginning of the COVID-19 pandemic has led to the implementation of distance learning (PJJ) in educational institutions, including UIN Syarif Hidayatullah Jakarta Objective. The purpose of this study was to examine the relationship of distance learning and symptoms of somatoform disorders with stress levels of UIN Syarif Hidayatullah Jakarta students in the early COVID-19 pandemic. Method. This study used an analytic observational with a quantitative approach, cross sectional study design. Respondents were 470 active students of UIN Syarif Hidayatullah Jakarta. Data were obtained by distributing questionnaires via online in April to May 2020. Multivariate analysis was performed using a multiple logistic regression test. Results. The frequency of PJJ had a significant relationship with respondents' stress levels. The results of multivariate analysis showed that university students who had PJJ ≥12 times were more likely to have low levels of stress compared to students with PJJ frequency of